Construction and validation of chemoresistance-associated tumor- infiltrating exhausted-like CD8+ T cell signature in breast cancer: cr-TILCD8TSig - Cai, DQ.; Cai, Diankui; Zou, Yiping; Chen, Xumeng; Jian, Zhixiang; Shi, Mude; Lin, Ye; Chen, Jueming (Frontiers in Immunology, 2023)
Background: Accumulating evidence has revealed that CD8+ T cell exhaustion (Tex) results in worse immunotherapy outcomes. However, the molecular functions and mechanisms of action of Tex in chemoresistance needed to be elucidated. Methods: The populations of tumor-infiltrating CD8+ T cells (TILCD8Ts) in chemoresistant and chemosensitive groups of the GSE25066 dataset were calculated using CIBERSORT. Differentially expressed genes (DEGs) between TILCD8Ts and other immune cells were explored by integrating 16 immune cell datasets downloaded from the gene expression omnibus (GEO) database. Gene ontology (GO)/Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment, univariate and multivariate Cox regression, and least absolute shrinkage and selection operator (LASSO) regression of TILCD8T-specific upregulated genes were used to construct a chemoresistant TILCD8T signature (cr-TILCD8TSig). Clinical prognostic data, genomic alterations, chemotherapy response, and immunotherapy response were compared between the different cr-TILCD8TSig subgroups in the GSE25066 and the cancer genome atlas breast cancer (TCGA-BRCA) cohorts. Results: A cr-TILCD8TSig with exhausted features was identified, consisting of seven genes (TCF7, RARRES3, ARL4C, ITK, CDH3, GZMB, and KLRD1), which were identified from 104 TILCD8Ts-specific DEGs. Our results showed that compared to the cr-TILCD8TSig-low subgroup, the -high subgroup had a poorer distant relapse-free survival (DRFS) in the GSE25066 cohort and worse progression-free survival (PFS) in the TCGA-BRCA cohort. Univariate and multivariate Cox regression analyses also demonstrated that cr-TILCD8TSig was an independent prognostic factor in the two independent cohorts. Furthermore, cr-TILCD8TSig-low patients benefited more from chemotherapy and immunotherapy than cr-TILCD8TSig-high patients. Besides, we found cell transmembrane signal transduction and the ECM may provide the molecular basis for resistance to antitumor agents in the cr-TILCD8Sig-high subgroup. For genomic alterations, we revealed that mutations in PIK3CA, DMD, and APOB were more common in the cr-TILCD8Sig-high subgroup than in the cr-TILCD8Sig-low subgroup. A nomogram was finally constructed with good discrimination and calibration. Conclusions: cr-TILCD8TSig is a useful tool to independently predict prognosis, chemotherapy response, and immunotherapy outcomes in patients with breast cancer.